Association between speech and high-frequency hearing loss and depression, anxiety and stress in older adults. (April 2018) - Jayakody, Dona M.P.; Almeida, Osvaldo P.; Speelman, Craig P.; Bennett, Rebecca J.; Moyle, Thomas C.; Yiannos, Jessica M.; Friedland, Peter L.
Highlights: More than one third of the world population above the age of 65 years suffers from age-associated hearing loss. There are common central neurological, anatomical and physiological processes affected by depression, anxiety and stress and hearing loss. The severity of depressive, anxiety symptoms and stress increase with the severity of hearing impairment. Abstract: Background: Age-related hearing loss (ARHL) and depression are considered leading causes of disability in older adults. This cross-sectional study investigated the association between the severity of speech and high-frequency ARHL and depression, anxiety and stress in older adults. Study design: Cross-sectional study of a community-derived sample of adult volunteers. Methods: A hearing assessment was completed by 151 participants (73 males and 78 females; M = 64.44 ± 10.77 years). Based on their better-ear speech (0.5, 1, 2, & 4 kHz) and high-frequency (6 & 8 kHz) hearing thresholds, they were divided three groups: those with normal hearing; those with mild to moderate hearing loss; and those with moderately severe to profound hearing loss. All participants also completed the Depression, Anxiety and Stress Scale (DASS-21). Results: A binomial logistic regression analysis revealed that the respective odds ratios (ORs) (95% confidence interval) of clinically significant depression, anxiety and stress for participants with a moderately severe to profound hearing loss across the speech frequency range were: 27.51 (3.25, 232.95), 5.89 (1.95, 17.73) and 5.64 (1.55, 20.48). Similarly, the respective ORs of clinically significant depression, anxiety and stress were 6.54 (0.75, 57.02), 6.21 (1.52, 25.33) and 5.32 (1.02, 27.75) for participants with moderately severe to profound hearing loss across high frequencies. The non-parametric Cuzik test revealed a statistically significant positive (p < .05) trend of association between both better-ear speech and high-frequency hearing loss and DASS scores. Conclusion: The observed graded associations suggest that hearing loss is a causative factor for clinically significant depression, anxiety and stress symptoms.